Intersectional Disadvantage: Exploring Differences Between Aboriginal and Non-Aboriginal Parents with Intellectual Disability in the New South Wales Child Protection System. Issue 2 (15th March 2018) - Collings, S.; Dew, A.; Gordon, T.; Spencer, M.; Dowse, L.
ABSTRACT: Background : Parents with intellectual disability and Aboriginal and Torres Strait Islander parents are overrepresented in child removal but research has not explored the intersection of Aboriginality and intellectual disability in child protection. Methods : A case file review of 45 parents with intellectual disability ( n = 14 Aboriginal and n = 31 non-Aboriginal) engaged in care proceedings in New South Wales was undertaken. Parent and child demographics and investigation triggers and outcomes were compared. Results : Aboriginal parents were significantly younger than non-Aboriginal parents at initiation of an investigation, twice as likely to be investigated due to concerns about parenting capacity, and more likely to have children removed than non-Aboriginal parents. Conclusion : The intersection of Aboriginality and intellectual disability appears to increase the risk of negative encounters with child protection systems. Targeted support for young Aboriginal parents and greater disability awareness and cultural sensitivity by child welfare workers are needed.